KINERJA PENGAWAS DALAM MENINGKATKAN KEMAMPUAN KEPALA SEKOLAH PADA MAN JANARATA KABUPATEN BENER MERIAH - Tajerian Hasan; Djailani AR; Rusli Yusuf (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2012)
Abstract: One of factor in improving the ability of the headmaster is the schoolsupervisor. This study aims to determine the pattern of the ways to motivate supervisors, discipline supervisor, supervisors preparation program, and the constraints faced by supervisors in improving the performance of headmaster in MAN Janarata district Bener Meriah. This study used a qualitative approach with descriptive methods. The technique of collecting data through observation, interviews, and study documentation. Research subjects is school supervisor, headmaster, MGMP leader, and teacher. The results showed: (1) Provisionmotivation by school supervisor shaped career development opportunities, seminars, continuing education, participation in target setting, recognition and clear expectations. (2) fostering supervisory discipline in improving the performance of school principals in MAN Janarata district Bener Meriah is do with persuasive approach in guiding of headmaster, supervising headmaster, and determine job description to the headmaster as well as giving sanction to the principal in accordance with the level of the infraction. (3) PreparationProgram by establishing the quality policy, setting performance indicators and targets, implementing quality improvement. (4) In hibiting factores school supervisor in improving the performance of headmaster include: lack of socialization of school rules, lack of coordination of school, lack of work discipline.Keyword: Performance and Supervisors